2019
DOI: 10.3390/computers8030059
|View full text |Cite
|
Sign up to set email alerts
|

RNN-ABC: A New Swarm Optimization Based Technique for Anomaly Detection

Abstract: The exponential growth of internet communications and increasing dependency of users upon software-based systems for most essential, everyday applications has raised the importance of network security. As attacks are on the rise, cybersecurity should be considered as a prime concern while developing new networks. In the past, numerous solutions have been proposed for intrusion detection; however, many of them are computationally expensive and require high memory resources. In this paper, we propose a new intru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Furthermore, RNN algorithms have been used in various applications including Heating, Ventilation, and Air Conditioning (HVAC) systems [34][35][36]; nonoccupied buildings' energy prediction [37]; image pattern recognition [38]; and intrusion detection systems [12,39,40] all with significant results. Moreover, according to the results of Cerkez et al [41] and Abdelbaki et al [42], simple encounters can represent neurons in RNN and, hence, easy hardware implementation.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, RNN algorithms have been used in various applications including Heating, Ventilation, and Air Conditioning (HVAC) systems [34][35][36]; nonoccupied buildings' energy prediction [37]; image pattern recognition [38]; and intrusion detection systems [12,39,40] all with significant results. Moreover, according to the results of Cerkez et al [41] and Abdelbaki et al [42], simple encounters can represent neurons in RNN and, hence, easy hardware implementation.…”
Section: Related Workmentioning
confidence: 99%
“…RNNs have been used extensively for pattern recognition [19]. However, a little research has been reported to analyse the effectiveness of RNNs for intrusion detection systems using NSL-KDD dataset, such as our previous work at [3]. RNN has recently got colossal attention due to its less complexity and better generalisation capabilities.…”
Section: Adversarial Random Neural Network Modelmentioning
confidence: 99%
“…Network security is now considered as one of the primary issues faced by modern computer networks. A significant extension of intelligent services to the users has raised strong concerns among the research communities to design and develop efficient intrusion detection systems (IDS) [3]. Not only does it enforce the safety of the communication system, but it could also be useful as an alternative to traditional firewalls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations